Weathering Processes and Mechanisms of Low-Grade Metamorphic Rock following Freeze-Thaw Processes. (22nd February 2023) - Wu, Guopeng; Cui, Kai; Wang, Pei; Chen, Wenwu
Abstract : A remarkable risk in the field of rock engineering is the natural exposure of low-grade metamorphic rock to the freeze-thaw process. Examples of such materials are slate and phyllite, which are employed approximately mountainous permafrost zones. In order to study the weathering processes and mechanisms in low-grade metamorphic rock following freeze-thaw weathering processes, the freeze-thaw cycles were applied. Accordingly to this process, low-grade metamorphic rock partially or completely deteriorates, and mechanical properties, microstructure, and mineral content changes are commonly associated with freeze-thaw processes. This study shows that, following numerous freeze-thaw cycles processes, the quality, wave velocity, and compressive strength of rock reduce; calcite, mica, feldspar, and pyrite contents decrease; and clay minerals and gypsum content increase. Furthermore, the study also demonstrated that the changes in quality, wave velocity, and compressive strength caused by weathering of the rock followed the sequence slate > phyllite. However, the mineral contents of slate and phyllite alter in the same way. Because of this increase in volume and subsequent F-T cycles, new cracks form on the surfaces of pores due to outward pressure, and a lot of water is absorbed by clay minerals. The amount of water increases once again due to freezing as the temperature falls below zero degrees Celsius. This course duplicates with cyclic temperature changes and causes deterioration of low-grade metamorphic rock materials. By analysis of an examination of the damage variables based on wave velocity, it is possible to conclude that mineral changes during the freeze-thaw effect may make for the formation of voids and the deterioration of metamorphic rock. This research contributes to a better understanding of weathering processes and mechanisms of low-grade metamorphic rock following freeze-thaw weathering processes.